2022
DOI: 10.11591/ijphs.v11i1.21159
|View full text |Cite
|
Sign up to set email alerts
|

Post-locked down mental wellbeing among Malaysian adults: factors of life satisfaction in urban Malaysia

Abstract: Under the enforcement of the recovery movement control order (RMCO), citizens of Malaysia were allowed to commute for work with tight protocols of social distancing. In this period of time, most individuals were adjusting to the new norm after being locked down for about six weeks. With an assumption that the social dynamics could have been different from the pre-pandemic era, this study aims to investigate how mattering predicts life satisfaction among individuals who live in the urban area of western Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(75 reference statements)
0
0
1
Order By: Relevance
“…In another study, PSS was found to positively linked SWL, where subjects with greater PSS were found to experience less stress and have better interpersonal relationships, and reported higher SWL [9]. However, our results indicated that mattering did not significantly predict SWL and it is inconsistent with the previous studies in the same context of Malaysian urbanites amidst the outbreak [31]. It can be explained by the fact that in the Malaysian context, the prolonged social distancing enforcement had increased the levels of anxiety and depression [22], among individuals with lower levels of mattering; which lowered the impact of mattering on their SWL.…”
Section: Discussioncontrasting
confidence: 99%
“…In another study, PSS was found to positively linked SWL, where subjects with greater PSS were found to experience less stress and have better interpersonal relationships, and reported higher SWL [9]. However, our results indicated that mattering did not significantly predict SWL and it is inconsistent with the previous studies in the same context of Malaysian urbanites amidst the outbreak [31]. It can be explained by the fact that in the Malaysian context, the prolonged social distancing enforcement had increased the levels of anxiety and depression [22], among individuals with lower levels of mattering; which lowered the impact of mattering on their SWL.…”
Section: Discussioncontrasting
confidence: 99%